Dual-enhanced photothermal conversion properties of reduced graphene oxide-coated gold superparticles for light-triggered acoustic and thermal theranostics() - Lin, Li-Sen (Nanoscale, 2016)
A rational design of highly efficient photothermal agents that possess excellent light-to-heat conversion properties is a fascinating topic in nanotheranostics. Herein, we present a facile route to fabricate size-tunable reduced graphene oxide (rGO)-coated gold superparticles (rGO-GSPs) and demonstrate their dual-enhanced photothermal conversion properties for photoacoustic imaging and photothermal therapy. For the first time, graphene oxide (GO) was directly used as an emulsifying agent for the preparation of gold superparticles (GSPs) with near-infrared absorption by the emulsion method. Moreover, GO spontaneously deposited on the surface of GSPs could also act as the precursor of the rGO shell. Importantly, both the plasmonic coupling of the self-assembled gold nanoparticles and the interaction between GSPs and rGO endow rGO-GSPs with enhanced photothermal conversion properties, allowing rGO-GSPs to be used for sensitive photoacoustic detection and efficient photothermal ablation of tumours in vivo. This study provides a facile approach to prepare colloidal superparticles–graphene hybrid nanostructures and will pave the way toward the design and optimization of photothermal nanomaterials with improved properties for theranostic applications.